Systems analysis design methods - Whitten, Jeffrey L. (McGraw-Hill/Irvin, 2004)
This work aims to balance the coverage of concepts, techniques and their applications, provide the most examples of system analysis and design deliverables available, and balance the coverage of classical methods and emerging methods.